Dynamics of Hate Speech in Media Politics Social: Analysis of Fufufafa's Case Footprint on Facebook - Purnomo, Anisya Septiawati; Faradilah, Nur; Hafair, Arya Putra; Nisa, Pia Khoirotun (Raudhah Publisher, 2025)
Social media has become a platform that facilitates global interaction instantly. However, with this ease of access, the phenomenon of hate speech has emerged that affects political and social dynamics. The study analyzed the trail of